2009
DOI: 10.1063/1.3076247
|View full text |Cite
|
Sign up to set email alerts
|

Topological chaos and mixing in a three-dimensional channel flow

Abstract: Passive mixing is investigated in a mathematical model of steady, three-dimensional, laminar flow through a rectangular channel. Efficient stirring is achieved by imposing spatially periodic transverse boundary velocities that generate asymmetric, counter-rotating rolls aligned with the channel axis. The flow is designed and analyzed using the concept of topological chaos, in which complexity is embedded in the flow through the motion of periodic orbits. A lid-driven flow producing topological chaos is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In dynamical systems applications, these surfaces are typically two-dimensional physical space and the maps act in time, but under certain conditions maps can also be constructed in three-dimensional space. 32 An isotopy class consists of all the topologically equivalent diffeomorphisms that can be mapped to each other through a "fixed stirrer" diffeomorphism in which the punctures are fixed relative to each other during the mapping. According to the TNCT, each isotopy class contains a representative homeomorphism U, the Thurston-Nielsen (TN) representative, that is one of three possible types: finite order (FO), pseudo-Anosov (PA), or reducible.…”
Section: -21mentioning
confidence: 99%
“…In dynamical systems applications, these surfaces are typically two-dimensional physical space and the maps act in time, but under certain conditions maps can also be constructed in three-dimensional space. 32 An isotopy class consists of all the topologically equivalent diffeomorphisms that can be mapped to each other through a "fixed stirrer" diffeomorphism in which the punctures are fixed relative to each other during the mapping. According to the TNCT, each isotopy class contains a representative homeomorphism U, the Thurston-Nielsen (TN) representative, that is one of three possible types: finite order (FO), pseudo-Anosov (PA), or reducible.…”
Section: -21mentioning
confidence: 99%
“…Moreover, Stremler & Chen [10] suggested that a modified two dimensional cavity flow, featuring vortical motion with three or more well-defined ghost rods, could be used to obtain effective mixing. Chen & Stremler [3] further suggested that this vortical lid driven flow could provide efficient lateral mixing for a pressure driven, continuous flow mixer. Though hypothetical at this stage, this continuous flow mixer shows promising potential and bears a strong qualitative resemblance to the realistic micromixer of Kang et al [7].…”
Section: Ghost Rodsmentioning
confidence: 99%
“…Section 2 begins by proposing an analogue of braiding in three dimensions. Section 3.1, following the methodology of Stremler and Chen [10,3], proposes a hypothetical batch mixer capable of executing these three dimensional 'braiding' protocols. The efficiency of each protocol is assessed using surface tracking (Section 3.2) and compared with theoretical predictions (Section 4).…”
Section: The Next Frontier: From 2d To 3dmentioning
confidence: 99%
“…The final feature that we wish to point out is that the ''axial flow'' in this kinematic model is independent of the location in the crosssection. This could be dealt with by modeling the axial flow with an applied Poiseuille flow (as is done in Stroock and McGraw (2004), Chen andStremler (2009), Song et al (2008), for example). However, if the flow was driven by the electro-osmotic force, rather than pressure, this would not be an issue (Pacheco (2008)).…”
Section: A Kinematic Model For Multiple Secondary Flowsmentioning
confidence: 99%
“…This question has been addressed using computational fluid dynamics techniques by Aubin et al (2005) and Yang et al (2005). Models of the SHM based on lid driven cavity flows have been considered by Stroock and McGraw (2004), Chen andStremler (2009), andSong et al (2008), where the walls, with the imposition of no-slip boundary conditions, are moved in a way that simulated the secondary flows generated by the herringbone patterns and the axial motion of the fluid is governed by an imposed pressure driven Poiseuille flow.…”
Section: Introductionmentioning
confidence: 99%